Does Sexual Self-Concept Ambiguity Moderate Relations Among Perceived Peer Norms for Alcohol Use, Alcohol-Dependence Symptomatology, and HIV Risk-Taking Behavior? - Talley, Amelia E (Rutgers University, 2014)
OBJECTIVE: The current study examines the relation between peer descriptive norms for alcohol involvement and alcohol-dependence symptomatology and whether this relation differs as a function of sexual self-concept ambiguity (SSA). This study also examines the associations among peer descriptive norms for alcohol involvement, alcohol-dependence symptomatology, and lifetime HIV risk-taking behavior and how these relations are influenced by SSA. METHOD: Women between ages 18 and 30 years (N = 351; M = 20.96, SD = 2.92) completed an online survey assessing sexual self-concept, peer descriptive norms, alcohol-dependence symptomatology, and HIV risk-taking behaviors. Structural equation modeling was used to test hypotheses of interest. RESULTS: There was a significant latent variable interaction between SSA and descriptive norms for peer alcohol use. There was a stronger positive relationship between peer descriptive norms for alcohol and alcohol-dependence symptomatology when SSA was higher compared with when SSA was lower. Both latent variables exhibited positive simple associations with alcohol-dependence symptoms. Peer descriptive norms for alcohol involvement directly and indirectly influenced HIV risk-taking behaviors, and the indirect influence was conditional based on SSA. CONCLUSIONS: The current findings illustrate complex, nuanced associations between perceived norms, identity-related self-concepts, and risky health behaviors from various domains. Future intervention efforts may be warranted to address both problem alcohol use and HIV-risk engagement among individuals with greater sexual self-concept ambiguity.